2017
DOI: 10.1016/j.neurobiolaging.2017.03.034
|View full text |Cite
|
Sign up to set email alerts
|

The frequency and influence of dementia risk factors in prodromal Alzheimer's disease

Abstract: ArtikkelitTerveystieteiden tiedekunta 2017The frequency and influence of dementia risk factors in prodromal This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 36 publications
(35 reference statements)
3
23
0
1
Order By: Relevance
“…Lobo et al 36 did not find less MMSE decline in light drinkers than in abstainers. Bos et al 37 recently reported increased risk of cognitive decline (non Alzheimer types) with increased alcohol. Others have found a protective effect of moderate alcohol use only in those not carrying the ApoE4 allele (a risk gene for late-onset Alzheimer’s disease) 38…”
Section: Resultsmentioning
confidence: 99%
“…Lobo et al 36 did not find less MMSE decline in light drinkers than in abstainers. Bos et al 37 recently reported increased risk of cognitive decline (non Alzheimer types) with increased alcohol. Others have found a protective effect of moderate alcohol use only in those not carrying the ApoE4 allele (a risk gene for late-onset Alzheimer’s disease) 38…”
Section: Resultsmentioning
confidence: 99%
“…CSF samples from the SPIN cohort have contributed to several international multicenter CSF biomarker studies [34][35][36][37][38]. The SPIN cohort has contributed to the characterization of different CSF biomarkers such as b-site APP-cleaving enzyme activity [39,40], sAPP-b [6,39,41], neurofilament light chain [41], YKL-40 [6,39,[41][42][43], progranulin [44], a panel of synaptic proteins [45], and mitochondrial DNA [46] in different neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies suggest that the majority of cognitively normal individuals have low densities of NFT [104] with Braak stages 1/2 being characteristic of cognitively normal individuals and higher stages of at least mild cognitive impairment (MCI), and there is also less astrocytosis and microglial reaction [41]. By contrast, Bouras et al [32] found that all non-demented cases had NFT in layer II of the entorhinal cortex and in sector CA1 of the HC. Moreover, in non-demented individuals, NFT were more numerous in medial temporal lobe (MTL) regions and in cortical association areas when a memory deficit was present suggesting NFT could be related to memory loss in non-demented individuals [70].…”
Section: Risk Factors Agementioning
confidence: 99%